Potensi Metode 1:4:P:C:R untuk Mengembangkan Keterampilan Berpikir Kritis dan Kreatif - Eunice Widyanti Setyaningtyas (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
This article discusses about the implementation of 1:4:P:C:R teaching and learning method related to its potential to stimulate critical and creative thinking skill of the students. This is based on the fact that critical and creative thinking skills has never been an out-to-dated discussion in education as it has to be taught and trained to prepare the students function well in all aspects in professional and private life. Therefore, lecturers need to design instruction that can help students teachers learn and develop their capacity of thinking critically and creatively. It is hoped that the discussion can be a useful inspiration for other lecturers in applying the critical and creative thinking strategies in their classes. This article is a result of observation in Curricullum and Learning subject in three classes using the 1:4:P:C:R method in the Elementary School Teacher Training and Education, UKSW. This observation study functions as a preliminary study before doing further research. The result showed that 1:4:P:C:R could start the student teachers to think critically because students had to give information to their peers in the area of material in which their peers are lacking, also to think creatively as students needed to create a product to show their knowledge to others.